Building a Positive School Image: Brand Image Strategy in the Competition of Private Educational Institutions - Meirina Khusnul Azizah; Harisatunisa; Mughni Zaenal Mukhtar (Universitas Islam Negeri Walisongo, 2026)
The increasingly competitive landscape of educational institutions requires adaptive brand management strategies to build reputation and competitiveness. This study aims to analyze brand management strategies at Lajnah Pendidikan dan Pengajaran (LPP) Al-Irsyad Al-Islamiyyah Purwokerto using the theoretical framework of Kevin Lane Keller and M. G. Swaminathan, focusing on the dimensions of favorability, strength, and uniqueness. This study employs a descriptive qualitative method through observation, interviews, and documentation studies. The findings reveal that in the favorability dimension, a positive image is built through consistent service quality, teacher professionalism, and staff loyalty, which foster parental trust. The strength dimension is reflected in high market demand, with a student selection ratio of 3:1, and strong alumni networks. Meanwhile, the uniqueness dimension is represented through a glocal curriculum (integration of the International Baccalaureate and Islamic values) and the global Muadalah network. This strategy has proven effective in creating sustainable competitive advantages and enhancing institutional reputation at both national and international levels. This study suggests that other educational institutions adopt the integration of local values and global standards as a strong brand differentiation.